Clinical and histological effects of the intrathecal administration of methylprednisolone in dogs - Lima, Rodrigo Moreira [UNESP] (2010)
Background: Methylprednisolone is one of the most commonly used steroids for management of chronic back pain via epidural injection. Its inadvertent injection into the intrathecal space is associated with complications such as adhesive arachnoiditis. Objective: The present study aimed to assess the clinical and histological changes associated with the injection of methylprednisolone into the intrathecal space of dogs. Study Design: A randomized, double blind, controlled animal trial. Methods: After approval by the animal research ethics committee, 14 dogs were studied in a randomized double blind controlled trial. They were assigned to one of 2 groups: Group I received 1 mL of 0.9% normal saline; Group II received 1 mL (1.15mg/kg) of methylprednisolone into the intrathecal space. Animals were clinically evaluated for 21 days, and then sacrificed. The lumbar and sacral portions of their spinal cords were removed for histological examination. Results: In Group I, there were no clinical or histological changes. All animals in Group II showed no clinical changes but all exhibited histological changes in the spinal cord. The main histological changes consisted of meningeal thickening and lymphocytic infiltrates in the blood vessels. In 3 animals, adhesion of pia, arachnoid, and dura matter was noted and the nerve roots were surrounded by fibrosis. In one animal, necrosis of the spinal cord was evident. Limitations: The limitations of the present study include: small sample of animals (n=14), relative short clinical follow-up (21 days), and use of a commercially available drug solution, which is not preservative free. Conclusion: The present study demonstrated that the intrathecal administration of commercially available methylprednisolone was responsible for causing histological changes in the spinal cord and meninges of the animals studied.